Robert Bruce and the community of the realm of Scotland - Barrow, G. W. S. (Edinburgh Classic Editions Series., 2005)
Amidst this healthy climate of divergence and debate, Robert Bruce and the Community of the Realm of Scotland has continued to provide an authoritative and accessible analysis of the history of Scotland between 1286 and 1329. It presents a portrait of an era and a study of its central figure which is a masterpiece of historical writing. The reach and impact of this book has travelled well beyond Scotland.' - Michael Brown, University of St Andrews 'This magnificient study of Scotland's hero king is the masterwork of Professsor Geoffrey Barrow, one of the nation's greatest medievalists of the modern era. First published nearly half a century ago, it remains without compare as the book on Robert the Bruce.' - Professor Tom Devine, Personal Senior Research Professor of History, University of Edinburgh This classic edition of the definitive history of Robert Bruce's life and career, during Scotland's tumultuous coming of age in the Wars of Independence, is one of the twentieth century's bona-fide classics in historical writing. It tells the story of how Robert Bruce outwitted Edward I, defeated his son, Edward II and in so doing secured independence for Scotland. First published in 1965, Robert Bruce was quickly recognised as an indispensable guide to understanding Scotland's complex game of thrones and its medieval society. The central theme of this crucial work remains the interplay and tension between Bruce himself and the very concept of a Scottish nation, of which Bruce aspired to be king. The chief shift in emphasis in this history was to demonstrate the continuity and unity of purpose which linked the stake-holders of a nascent Scottish realm throughout the period from 1290 to 1329. In this bloody period of political intrigue, battlefield heroism and variable loyalties, a singularly Scottish identity was born in campaigns against English claims, culminating in the Battle of Bannockburn in June 1314, the fulcrum around which Bruce built a nation and a Scottish peace. Geoffrey Barrow is perhaps Scotland's most valued and cited of medieval historians. He was Sir William Fraser Professor of Scottish History and Palaeography, University of Edinburgh, 1979-92, where he is currently Professor Emeritus.